Physicochemical Characterization of Goroho Banana (Musa acuminafe sp.) Starch and Its Potential as a Binder in Tablet Formulation - Elvie Rifke Rindengan; Rilyn Novita Maramis; Evelina Maria Nahor (Jurnal FARMASIMED (JFM), 2026)
Starch is a commonly used excipient in pharmaceutical formulations due to its favorable physicochemical properties. Bananas represent a promising natural source of starch. One potential source is Goroho banana (Musa acuminata), an endemic plant from North Sulawesi that remains underexplored as a pharmaceutical excipient. This study aimed to characterize the physicochemical properties of starch isolated from unripe goroho banana and to evaluate its potential as a binder in tablet formulation. The starch was isolated and subsequently subjected to physicochemical characterization. Chemical characterization included proximate analysis (moisture, ash, fat, and protein content) and determination of amylose and amylopectin content. Physical characterization involved the observation of starch granule morphology using scanning electron microscope (SEM) and the analysis of gelatinization profile using rapid visco analyzer (RVA). The obtained starch yield was 7.66%, with a slightly brownish-white appearance. The gelatinization temperature was recorded at 74.35 °C, and the pH of 1% starch dispersion was 7.76. Morphological analysis revealed that the starch granules were oval to spherical in shape with relatively smooth surfaces. Tablet formulation evaluation showed that all formulations met the requirements for weight uniformity and disintegration time (<15 minutes). Formulations F3 and F4 complied with the hardness requirement, while all formulations exhibited friability values >1%, indicating that they did not meet the acceptable friability standard. These findings suggest that goroho banana starch possesses suitable physicochemical characteristics for use as a pharmaceutical excipient, particularly as a binder. However, further formulation optimization is required to improve the mechanical strength of the resulting tablets.